Answer:
B (5, 13)
Step-by-step explanation:
9x + 4y = 97
9x + 6y = 123
To solve by elimination, we want to <em>eliminate</em> a variable. To do this, we must make one variable cancel out.
First, we can see that both equations have 9x. To cancel out x, we must make <em>one</em> of the 9x's <em>negative</em>. To do this, multiply <em>each term</em> in the equation by -1.
-1(9x + 6y = 123)
-9x - 6y = -123
This is one of your equations. Set it up with your other given equation.
9x + 4y = 97
-9x - 6y = -123
Imagine this is one equation. Since every term is negative, you will be subtracting each term.
9x + 4y = 97
-9x - 6y = -123
___________
0x -2y = -26
-2y = -26
To isolate y further, divide both sides by -2.
y = 13
Now, to find x, plug y back into one of the original equations.
9x + 4(13) = 97
Multiply.
9x + 52 = 97
Subtract.
9x = 45
Divide.
x = 5
Check your answer by plugging both variables into the equation you have not used yet.
-9(5) - 6(13) = -123
-45 - 78 = -123
-123 = -123
Your answer is correct!
(5, 13)
Hope this helps!
Work seriously and you will be eable to answer
Answer:
12x - 15 dollars
Step-by-step explanation:
Sunny earns $12 per hour for delivering cakes.
She worked for x hours this week.
Unfortunately, she was charged $15 for a late delivery on Tuesday
She was supposed to earn $12 × x = $12x this week
But she was charged $15 for late delivery on Tuesday
So her net earning this week is; $12x - $15
Answer:
Incorrect
Step-by-step explanation:
The fraction of 6/12 all squared gives 36/144 36/36 and 144/36 reduces to 1/4.